Credit Risk Determinants in the Chinese Banking Industry - He, Ran (2010)
This thesis studies credit risk determinants in the Chinese banking industry. Generally speaking, bank credit risk is influenced by macroeconomic conditions, counterparty characteristics, and bank-specific factors. Various credit risk assessing models could be used to quantify the effects of different credit risk determinants. Chinese banks are researching and developing appropriate and advanced credit risk systems to narrow the gap with foreign banks. This paper establishes and estimates a credit risk model for the Chinese banking industry taking into account the data for the period from 2002 to 2009. The empirical results suggest a significant and fairly robust relationship between credit risks and key factors including the microeconomic factors (total loan ratio, loan loss provision, tier 1 capital ratio, and bank size) and macroeconomic factors (gross domestic product (GDP) growth, consumer price index (CPI) growth, and unemployment rate). The author also raises the issue of whether the determinants of non-performing loans are or are not similar between national commercial banks (NCBs) and urban commercial banks (UCBs). By comparing the regression results, it is found that five factors: total loan ratio, tier 1 ratio, bank size, GDP growth and unemployment rate, have major influences on NCB credit risk, meanwhile, UCB credit risk is significantly affected by loan loss provision, tier 1 ratio, CPI growth and unemployment rate.